   Symbol

# Calculator search results

Formula
Solve the equation Graph
$y = 2 x - 4$
$y = 2 \left ( x - 1 \right ) + 3$
$x$Intercept
$\left ( 2 , 0 \right )$
$y$Intercept
$\left ( 0 , - 4 \right )$
$x$Intercept
$\left ( - \dfrac { 1 } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , 1 \right )$
$2x-4 = 2 \left( x-1 \right) +3$
 Do not have the solution 
Solve the equation
$2 x - 4 = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) + 3$
 Multiply each term in parentheses by $2$
$2 x - 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } + 3$
$2 x - 4 = 2 x \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Add $- 2$ and $3$
$2 x - 4 = 2 x + \color{#FF6800}{ 1 }$
$2 x - 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } + 1$
 Move the variable to the left-hand side and change the symbol 
$- 4 = 1$
$\color{#FF6800}{ - } \color{#FF6800}{ 4 } = \color{#FF6800}{ 1 }$
 This equation is false because all of the values calculated by all terms are different 
 Do not have the solution 
$2 x - 4 = 2 x + 1$
Solve the fractional equation
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } \right ) \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Simplify the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 4 } = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture